Reallocating Content Coverage in Principles of Microeconomics to Increase Student Learning - Saunders, Phillip; Powers, John R. (American Economic Review, 1995)
The data base compiled during the norming of the Third Edition of the Test of Understanding College Economics (TUCE III) (Saunders, 1994) contains information from 40 instructors of introductory microeconomics courses at 26 different schools who used the posttest score to determine some part of their students' course grade. Of these students, 1,896 answered 30 questions on micro TUCE III both at the beginning (pretest) and the end (posttest) of their one-term course. This paper will use a comparison of the preand posttest responses to each alternative on each question by each student to analyze patterns of persistence and change in choosing correct and incorrect responses.' For each student on each question, there are five possible response patterns: